Application of improved BP neural network in fault detection of mine ventilation system - ZHANG Fei; HE Ya-qin; ZHANG Ke (Gong-kuang zidonghua, 2013)
For problem that step of traditional learning algorithm of BP neural network is difficult to determine, the paper proposed a method of using BP neural network based on RLS algorithm to detect fault of mine ventilation system. It introduced structure of the BP neural network briefly, and introduced RLS learning algorithm and simulation process in details. The simulation results show that the BP neural network with RLS algorithm can meet the requirements of fault detection of mine ventilation system.